Digestibilidade aparente de rações contendo levedura íntegra, levedura autolisada e parede celular pela tilápia do Nilo - Hisano, Hamilton; Sampaio, Fernanda Garcia; Barros, Margarida Maria [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (Inst Pesca, 2008)
Apparent digestibility coefficient of dry matter, crude protein, ether extract, gross energy, of diets supplemented with spray dried whole yeast (1.0; 2.0 e 3.0%), autolyzed (1.0; 2.0 e 3.0%), yeast cell wall (0.1; 0.2 e 0.3%) plus a additional diet with no yeast and yeast derivatives were evaluated to Nile tilapia. Eighty juveniles (83.0+/-8.5g) were placed in eight 250L aquaria for feeding and four aquaria of the same volume for collecting faecal samples. Both sets were equipped with flow-trough recirculation system provided with mechanical and biological filter. Diets supplemented with whole yeast, autolyzed yeast, and yeast cell wall presented, as mean, superior apparent coefficient digestibility than control. It can be concluded that supplementation of yeast and yeast derivatives improve apparent coefficient digestibility of experimental diets and diets supplemented with estimated level of 2.13-2.36% autolyzed yeast shows better digestibility.
Apparent digestibility coefficient of diets supplemented with whole yeast, autolyzed yeast and yeast cell wall by nile tilapia
Keywords: Saccharomyces cerevisiae; Oreochromis niloticus; glucans; mannans